INTERPRETATION OF SIMILES IN THE SCENE OF LITERARY WORLD (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is devoted to inform interpretation of simile in the scene of literary world using Uzbek, Russian and other linguist scientist’s viewpoints, opinions on simile. Therefore, the main features, such as anthropology and related subjectivity, philosophical basis, special imagery, effective, aesthetic and moral illumination of reality, the unity of universality and individuality, related to social, national and other factors, historicity, continuity and dynamism, layering, ideality, imaginary nature, ambivalence are researched. Some English and Uzbek literary texts in which simile was used were analyzed.